2011
DOI: 10.3109/17518423.2011.586371
|View full text |Cite
|
Sign up to set email alerts
|

Parental disciplinary practices following acquired brain injury in children

Abstract: Dysfunctional parenting practices, if not ameliorated, could exacerbate problematic child behaviour following ABI, as well as parent and family difficulties. Parental assessment may be useful as a method of screening for parental factors that put children at risk for ongoing behaviour problems and families for ongoing stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…What is more, when parents reported greater psychological distress, they were less likely to employ positive parenting approaches to manage post-TBI challenging behaviour. Woods et al (2011) reported similar findings and suggested that dysfunctional parenting practices potentially exacerbate challenging child behaviours following TBI and should be a target of post-injury behavioural interventions.…”
Section: Introductionsupporting
confidence: 68%
“…What is more, when parents reported greater psychological distress, they were less likely to employ positive parenting approaches to manage post-TBI challenging behaviour. Woods et al (2011) reported similar findings and suggested that dysfunctional parenting practices potentially exacerbate challenging child behaviours following TBI and should be a target of post-injury behavioural interventions.…”
Section: Introductionsupporting
confidence: 68%
“…Given that family function is a potentially modifiable risk factor, this finding indicates that attention to family stress and burden may enhance the quality of the child's environment with secondary benefits to the child. Indeed, growing evidence suggests that, following child brain insult, family and parent-based behavioral interventions are able to reduce parent stress and psychopathology, and improve children's behavior and social competence (Wade, Carey, & Wolfe, 2006;Woods, Catroppa, & Anderson, 2012;Woods, Catroppa, Barnett, & Anderson, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With investigations indicating that the family environment can help moderate the negative behavioural impact of childhood brain injury (Anderson et al, 2005;Hooper et al, 2007;Rivara et al, 1993Rivara et al, , 1996Woods et al, 2011), rehabilitation specialists have endeavoured to deliver interventions that incorporate an even greater family emphasis (Braga et al, 2005;van't Hooft and Norberg, 2010;Wade et al, 2006bWade et al, , c, 2008Wade et al, , 2012Woods et al, 2012. In a randomised-clinical trial (RCT), Braga et al (2005) compared a direct clinician delivered vs an indirect family supported (IFS) intervention for children with chronic impairment following traumatic brain injury (TBI).…”
Section: Introductionmentioning
confidence: 98%
“…Other families will "slip through the cracks", recognising that they do not have the necessary skills to ameliorate the ongoing problems. An inability to control their child's challenging behaviour can set in motion a course of maladaptive interactions that become firmly entrenched (Taylor et al, 2001;Woods et al, 2011).…”
Section: Introductionmentioning
confidence: 99%